The life of Elreta Melton Alexander : activism within the courts - Summey, Virginia L. (The University of Georgia Press, 2022)
"This book explores the life and contributions of groundbreaking attorney, Elreta Melton Alexander Ralston (1919-1998). In 1945, Alexander became the first African-American woman to graduate from Columbia Law School. In 1947, she was the first African-American woman to practice law in the State of North Carolina, and subsequently, in 1968, became the first African-American woman to become an elected district court judge. Despite her accomplishments, Alexander is little known to scholars outside of her hometown of Greensboro, North Carolina. Her life and career deserve recognition, however, not just because of her impressive lists of "firsts," but because she accomplished such impressive feats in the midst of the civil rights movement in the U.S. South. While Alexander did not actively participate in civil rights marches and demonstrations, she used her professional achievements and middle-class status to advocate for individuals who lacked a voice in the southern legal system. This book argues that Alexander was integral to the civil rights movement in North Carolina. Women like Alexander worked to change discriminatory laws while opening professional doors for other minority women. Women and African Americans have historically used the law as a means of obtaining personal and societal change, which was vital during the civil rights movement. Using her professional status, Alexander combatted segregation by demonstrating that black women were worthy and capable of achieving careers alongside white men, thereby creating environments in which other African Americans could succeed. Her legal expertise and ability to reach across racial boundaries made her an important figure in Greensboro, North Carolina history"-- Provided by publisher
Based on the author's thesis (doctoral - University of North Carolina at Greensboro, 2017) issued under title: Fighting within the bar : Judge Elreta Alexander and civil rights advocacy in Greensboro, North Carolina.
Keywords: Alexander-Ralston, Elreta, -- 1919-1998.; Alexander-Ralston, Elreta, -- 1919-1998; Femmes juges noires americaines -- Caroline du Nord.; Avocats de la defense penale -- Caroline du Nord.; Criminal defense lawyers -- North Carolina.; African American women judges -- North Carolina.; Electronic books.; Avocats de la défense pénale -- Caroline du Nord.; Femmes juges noires américaines -- Caroline du Nord.; Livres numériques.; e-books.; Criminal defense lawyers; African American women judges; North Carolina; Biography.; Biography; Biographies; Biographies.